The Effect Of Moringa Oleifera Leaf Extract On Cytotoxicity And Apoptosis Pathway In Breast Cancer Cell (Mcf-7) - Fisall, Umiey Fahietah Mohd (2019)
Moringa oleifera (MO) is belonging to Moringaceae family. In Malaysia, MO was known as „Munggai‟ or „Kelor‟ tree. MO is well known for its therapeutic properties that possesses a wide range of biological activities such as antioxidant and anticancer properties. The impact of different solvents of various degree of polarities on the cytotoxicity of breast cancer cell line (MCF-7), were studied. The cytotoxicity effect of 80 % methanol and its solvent fractions of Moringa oleifera leave (MOL) extract against MCF-7 cell were determined by using MTS assay. The normal breast cell line (MCF-10A) was used to compare with MCF-7 cell. The effective extract that gave the most cytotoxic effect on MCF-7 cell had been chosen. Among of all extracts, dichloromethane extract (DF-CME-MOL) had been selected accordingly to its lowest IC50 (5 μg/mL) and highest selectivity index (SI) (9.5). Then, the chosen extract (DF-CME-MOL) was proceed for further analysis. The phytochemical analysis was performed using DPPH, ABTS, Folin-Ciocalteu, aluminium chloride and GC-MS analysis.